Synthesis, characterization and biological studies of copper oxide nanostructures. (6th April 2018) - Jillani, Saquf; Jelani, Mohsan; Hassan, Najam Ul; Ahmad, Shahbaz; Hafeez, Muhammad
Abstract: The development of synthetic methods has been broadly accepted as an area of fundamental importance to the understanding and application of nanoscale materials. It allows the individual to modulate basic parameters such as morphology, particle size, size distributions, and composition. Several methods have been developed to synthesize CuO nanostructures with diverse morphologies, sizes, and dimensions using different chemical and physical based approaches. In this work, CuO nanostructures have been synthesized by aqueous precipitation method and simple chemical deposition method. The characterization of these products has been carried out by the x-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR) and UV–vis spectroscopy. Biological activity such as antibacterial nature of synthesized CuO is also explored. XRD peaks analysis revealed the monoclinic crystalline phase of copper oxide nanostructures. While the rod-like and particle-like morphologies have been observed in SEM results. FTIR spectra have confirmed the formation of CuO nanoparticles by exhibiting its characteristic peaks corresponding to 494 cm −1 and 604 cm −1 . The energy band gap of the as-prepared CuO nanostructures determined from UV–vis spectra is found to be 2.18 eV and 2.0 eV for precipitation and chemically deposited samples respectively. The antibacterial activity results described that the synthesized CuO nanoparticles showed better activity against Staphylococcus aureus . The investigated results suggested the synthesis of highly stable CuO nanoparticles with significant antibacterial activities.